Estimation of near surface attenuation parameter kappa (κ) in Northwest and Northeast Himalaya region. Issue 136 (September 2020) - Kumar, Vikas; Chopra, Sumer; Choudhury, Pallabee; Kumar, Dinesh
Abstract: We estimated the spectral decay parameter, kappa (κ) for the Northwest (NW) Himalaya and the Northeast (NE) Himalaya, particularly NE India, using the strong motion records obtained from accelerographs installed in these regions. We estimated κ from the horizontal as well as vertical records from 294 accelerograms (three components). It has been observed that in the NW Himalaya and NE India, the value of κ varies considerably among different sites. This may be due to the lateral heterogeneity of the crust in these regions. The estimated values of κ for the NW Himalaya and the NE India region do not vary with magnitude, which shows that κ is independent of the earthquake size. It was observed that the value of κ is more for the horizontal components as compared to vertical in both the regions. The local site conditions and tectonic regime influence the value of κ as it was found that κ is more at sites covered by alluvium than at rock sites, in both the regions. The average value of κ of horizontal and vertical components for the NW Himalaya is 0.050 ± 0.009s and 0.048 ± 0.010s, respectively. For the NE India region, the average value of κ of horizontal and vertical components is 0.0368 ± 0.0054s and 0.0334 ± 0.0091s, respectively, indicating that geological formations in the NE region are more competent (compact) and less attenuative. The high values of kappa indicate that most of the high frequency energy will be removed during strong earthquakes in these regions. The kappa values estimated for both the regions may be helpful for attenuation studies and updating hazard maps in these regions. Highlights: We estimate the spectral decay parameter, kappa (κ) for the Northwest Himalaya and the Northeast India regions using strong motion (SMA) records. We correlate between Kappa and epicentral distance, effect of geology and Vs30 in both the regions. These Kappa values can be used to model local site-effect to constrain high frequencies in a seismological model.